256-MSCT image acquisition with sequential axial scans: Evaluation of image quality and resolution in a phantom study - Klink, Thorsten; Nagel, H.; Schwartz, B.; Regier, M.; Adam, G.; Begemann, P. G. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: Evaluation of image quality and resolution of varying sequential axial scan protocols utilizing two resolution phantoms with a 256-MSCT scanner. Materials and Methods: Sequential axial scans were performed on a z-axis and an axial-plane resolution phantom with varying acquisition and reconstruction parameters. Two independent observers evaluated the image quality and resolution, and analyzed quantitative image quality parameters and radiation doses. Results: The best image quality and resolution were achieved with an activated z-flying focal spot (zFFS) and overlapping reconstruction. With an activated zFFS, image degradation was significantly minimized in marginal or overlapping zones of the beam, but the maximum effective detector width was reduced to 82% and 75%, respectively depending on the field of view. With a deactivated zFFS, the effective detector width was not restricted, but the image quality decreased and the artifacts increased as the collimation increased. Conclusion: For sequential axial CT data acquisition with multi-planar image reformation, the zFFS technique is crucial to achieve the best image quality and resolution. Major advantages are minimized image degradation and increased spatial resolution along the z-axis, but the zFFS reduces the maximum effective detector width. © Georg Thieme Verlag. KG Stuttgart, New York.
CRIS-Team Scopus Importer:2024-12-04
Keywords: 256-MSCT; artifacts; axial image acquisition; image quality and resolution; phantom; step and shoot